Disaster readiness of the College of Arts and Letters library, University of the Philippines, Diliman - Belmonte, Abel A. (2010)
Disasters are occurrences that cause destruction of property and livelihood at the afflicted area. Disasters have been a problem for libraries, and so disaster plans are made for libraries to be able to face and handle incoming disasters while having minimal loses. However, many libraries have neither disaster plans nor guidelines in making a disaster plan. Such is the case of the College of Arts and Letters Library (CAL Library). This study aims to create a set of guidelines to help the library make its own disaster plan.